2011
DOI: 10.21608/jfds.2011.81948
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Whole Eggs From Avian Species: A Comparative Study

Abstract: Egg weight and egg component, chemical composition, fatty acids and cholesterol, amino acids and minerals content in conventional eggs (ostrich, duck, hen and quail) were studied. Results indicated that, the ostrich egg had highest egg weight (g), and so had highest percent of weight and shell, while duck eggs showed highest percent of yolk. For chemical composition, Ostrich egg have had more highest moisture, carbohydrates and cholesterol contents, while highest values of protein, lipid and total ash were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…Such result was similar with Al-Obaidi and Al-Shadeedi (2017) and Uzochukwu et al (2017) who reported that the difference between cholesterol content of quail and chicken eggs may be due to the difference between the weight of the yolk of the quail egg and that of the chicken egg. While that result was differing from that according to Sharaf (2011) who recorded that cholesterol content of quail was higher than chicken eggs. The variability of these results may be due to variation in strain, feed, bird growth stage and environmental condition as recorded by Adeniyi et al (2016) Each value represents the mean of three replicates ±SD…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Such result was similar with Al-Obaidi and Al-Shadeedi (2017) and Uzochukwu et al (2017) who reported that the difference between cholesterol content of quail and chicken eggs may be due to the difference between the weight of the yolk of the quail egg and that of the chicken egg. While that result was differing from that according to Sharaf (2011) who recorded that cholesterol content of quail was higher than chicken eggs. The variability of these results may be due to variation in strain, feed, bird growth stage and environmental condition as recorded by Adeniyi et al (2016) Each value represents the mean of three replicates ±SD…”
Section: Discussioncontrasting
confidence: 80%
“…Statistical analysis revealed that a significant difference (P<0.05) was appeared in phosphor content. Similar finding was obtained by Sharaf (2011). Quail eggs had the lowest values of calcium, zinc, sodium and potassium content than chicken eggs.…”
Section: Minerals and Content Of Quail And Chicken Eggssupporting
confidence: 88%
“…This composition may be reflected by the binding of CON A (mannose), DSA, STA, AHA and ECA (GlcNAc), MAA and SNA‐1 (sialic acid) in the ostrich magnum glands, and the low levels of LTA, UEA and ALA stain (fucosyl residues), although inter‐species differences may exist. For instance, ostrich eggs have a higher proportion of firm albumin (77%) than those of the hen (57%; Fernández‐López et al 2006) and a higher percentage of carbohydrate (2.8% wet weight compared to 1.97% in the hen egg; Sharaf, 2011). In the domestic fowl, the shell of the egg also contains a glycosylated protein, ovocleidin, with glucosamine and galactosamine residues (Mann, 1999) which would be synthesized by the cells of the uterus since this area is where the shell is laid down.…”
Section: Discussionmentioning
confidence: 99%